Pelestarian Budaya Tenun Ikat Sebagai Warisan Ekonomi Dan Sosial Masyarakat Kabupaten Sabu Raijua - Windi Astuti Hana Kore; Hiwa Wonda (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Ikat weaving is one of Indonesia’s intangible cultural heritages that holds significant aesthetic, economic, and social value. Sabu Raijua Regency in East Nusa Tenggara is well known for its distinctive ikat textiles, characterized by unique motifs and a strong intergenerational transmission of weaving skills. However, modernization, competition from industrial textiles, and a decreasing interest among younger generations pose serious challenges to the continuity of this tradition. This article aims to analyze the preservation of Sabu Raijua ikat weaving as both a form of social heritage and an economic livelihood for the community. Using a qualitative, literature-based approach, the findings reveal that preservation efforts can be strengthened through cultural identity reinforcement, economic empowerment of weavers, product diversification, digital marketing, and proactive government involvement through regulations and training programs. This article further elaborates on the types of Sabu Raijua ikat textiles and their symbolic meanings.